(untitled) (Annals of Medical Research, 2023)
Aim: The aim of this study was to investigate whether sepsis-related mortality was associated with serum levels of interleukin (IL)-6, IL-10, tumor necrosis factor (TNF)-α, IL-6/IL-10 ratio and Glasgow Coma Scale (GCS), Acute Physiology and Chronic Health Evaluation (APACHE-II), Sequential Organ Failure Assessment (SOFA) scores. Materials and Methods: The sample of the study consisted of 50 patients (median age: 75 years) who were admitted to the Intensive Care Unit of the Emergency Department and were diagnosed with sepsis, between January 2019 and December 2019. Blood samples were drawn on day 1 and day 3 of hospitalization. The IL-6, IL-10, TNF-α levels, APACHE-II, SOFA, and GCS scores were recorded on a data collection form. Results: The deceased and the survivor groups significantly differed in day-1 (p = 0.013) and day-3 IL-6 (p = 0.016) levels, day-1 IL-6/IL-10 ratio (p = 0.029) and sex. There was no significant difference between the groups in day-1 and day-3 IL-10 levels and day-3 IL-6/IL-10 ratio. The GCS score was significantly lower in deceased subjects compared to survivors (p < 0.05). Conclusion: High IL-6 level and IL-6/IL-10 ratio at sepsis onset were found to be associated with mortality. IL-6 level may be particularly useful for predicting mortality if used in combination with scoring systems such as the GCS and different clinical parameters.